Endophytic mycobiota associated with Trifolium subterraneum growing under semiarid conditions. (17th December 2015) - Lledó, S.; Santamaría, O.; Rodrigo, S.; Poblaciones, M.J.
Abstract: Endophytic fungi were isolated from leaves and stems of Trifolium subterraneum at 10 sites in Extremadura (southwestern Spain), with the aims of (a) determining the fungal composition and its genetic variability and (b) analysing the effect of sampling site and tissue type on fungal diversity, frequency and species distribution. A total of 773 endophytic isolates were obtained from 100 plant specimens. Based on their morphological characteristics and internal transcribed spacer region (ITS) sequencing, a total of 54 species were identified. Most taxa were included in phylum Ascomycota, prevailing classes Dothideomycetes and Sordariomycetes. Almost 70% of the species showed a clear preference for one of the tissue types, showing clear organ specificity, and many of them had a very local distribution. For environmental variables, Mg in soil and precipitation had a significant influence on fungal diversity and species distribution. The leaf/stem fungal endophytes of T. subterraneum have been characterised for the first time. The results provide a reliable framework for further research on the functional roles of endophytes and eventual applications focused on this pasture species.